Gene Expression and Regulation in Mammalian Cells - Transcription Toward the Establishment of Novel Therapeutics 2018
DOI: 10.5772/intechopen.71866
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ribosomal RNA Transcription by Nutrients

Abstract: The ribosome is a unique machine for protein synthesis in organisms. The construction of ribosomes is exceedingly complex and consumes the majority of the cell materials and energy. The materials for ribosome production are supplied by nutrients. Therefore, the production of ribosomes is restricted by environmental nutrients, and cells need mechanisms to control ribosome production in order to reconcile demands for cell activities with available resources. Transcription of ribosomal RNA is an essential step in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 115 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…The ribosome is the cellular protein translation machine that controls growth across the whole organism and throughout life. Whilst there are several hundreds of rDNA gene copies available per cell, many are inactive physiologically through epigenetic mechanisms, and thus, the rate of transcription can be modulated by nutrient availability and other factors such as ageing [90][91][92]. rDNA silencing includes epigenetic regulation through hypermethylation of the rDNA promotor restricting Pol 1 binding and transcription, working alongside ribosome-associated proteins that coordinate Pol 1 activity and sense cellular environment [91,93].…”
Section: Blastocyst Nutrient Sensing Coordinates the Foetal Growth Trajectorymentioning
confidence: 99%
See 1 more Smart Citation
“…The ribosome is the cellular protein translation machine that controls growth across the whole organism and throughout life. Whilst there are several hundreds of rDNA gene copies available per cell, many are inactive physiologically through epigenetic mechanisms, and thus, the rate of transcription can be modulated by nutrient availability and other factors such as ageing [90][91][92]. rDNA silencing includes epigenetic regulation through hypermethylation of the rDNA promotor restricting Pol 1 binding and transcription, working alongside ribosome-associated proteins that coordinate Pol 1 activity and sense cellular environment [91,93].…”
Section: Blastocyst Nutrient Sensing Coordinates the Foetal Growth Trajectorymentioning
confidence: 99%
“…Lastly, we need to consider how environmental nutrient availability is perceived to regulate RRN3 expression and ribosome biogenesis. RRN3 expression is regulated by environmental factors, reduced by caloric and other nutrient restriction and sensitive to AA availability and mTORC1 signalling [91,92,102]. Indeed, PTEN, the negative regulator of mTORC1, has been proposed as a thrifty gene to drive metabolic storage when nutrients are plentiful [103].…”
Section: Blastocyst Nutrient Sensing Coordinates the Foetal Growth Trajectorymentioning
confidence: 99%
“…rRNA is the most abundant transcript of the cell and, as such, its transcription is highly energy consuming. In line with what is discussed above, rDNA transcription is modulated according to different environmental factors, like the regulators of cell cycle, growth factors, stressors, and nutrients, to guarantee energy homeostasis [26]. In particular, several studies reported that amino acid/glucose starvation and CR reduce rDNA transcription in yeast and mammal cells [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 52%
“…The ribosome is a unique machine to synthesize proteins in organisms 13,14 , and the control of ribosome biogenesis is a critical factor in the regulation of cellular activities 1518 . Because the level of rRNA transcription is a major factor determining the production of ribosomes, the regulation of rRNA transcription affects multiple cellular activities, including cell proliferation 13,14,16,1823 . Recently, increasing numbers of studies have shown that epigenetic regulators control rRNA transcription 13,14,2327 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the level of rRNA transcription is a major factor determining the production of ribosomes, the regulation of rRNA transcription affects multiple cellular activities, including cell proliferation 13,14,16,1823 . Recently, increasing numbers of studies have shown that epigenetic regulators control rRNA transcription 13,14,2327 . We previously showed that a JmjC histone demethylase, lysine-demethylase 2 A (KDM2A), decreases the dimethylated lysine 36 of histone H3 (H3K36me2) in the ribosome RNA gene (rDNA) promoter and represses rRNA transcription under starvation in breast cancer cells 28,29 .…”
Section: Introductionmentioning
confidence: 99%